2014
DOI: 10.1111/cei.12249
|View full text |Cite
|
Sign up to set email alerts
|

High-titre circulating tissue transglutaminase-2 antibodies predict small bowel villous atrophy, but decision cut-off limits must be locally validated

Abstract: SummaryNumerous studies suggest that high levels of circulating immunoglobulin (Ig)A tissue transglutaminase (TTG2) antibodies predict coeliac disease with high specificity. Accordingly, it has been suggested that duodenal biopsy may not be required routinely for diagnostic confirmation where quantitative serology identifies the presence of high antibody titres. However, defining a cut-off TTG2 threshold is problematic, as the multiple available assay methods are not harmonized and most studies have been focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 17 publications
4
31
0
Order By: Relevance
“…Studies continue to confirm our earlier paper7 showing that above such a threshold CD can be confidently diagnosed without recourse to a biopsy 3 5 6 8 9…”
supporting
confidence: 70%
“…Studies continue to confirm our earlier paper7 showing that above such a threshold CD can be confidently diagnosed without recourse to a biopsy 3 5 6 8 9…”
supporting
confidence: 70%
“…For the last 26 years, numerous studies evaluated only one serological marker in relation to intestinal pathology, mainly EMA and later on, tTg [8,9]. Fewer studies checked two antibodies, mainly IgA-tTg and IgA-EMA, the latest being in 2012-13 [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…After the discovery of the clinical value of immunoglobulin A (IgA) anti-tissue transglutaminase (tTG) antibody assay, which is the test of choice for detecting the disease, it was suggested that a histological assessment might be omitted in symptomatic children who have anti-tTG IgA levels 10-fold the upper reference limit (URL), as shown in data from some primary studies [50,51]. However, this is an arbitrary cutoff value, and a wide disparity of results and poor comparability, both between methods and between laboratories, has been reported [52]. Efforts to standardize and harmonize anti-tTG assays are therefore needed, particularly as the clinical goal, namely, the avoidance of an invasive examination, represents a major advantage for patients' safety and healthcare costs.…”
Section: Harmonization In Laboratory Medicine: Not Only Clinical Chemmentioning
confidence: 99%